Biodiversity of water borne conidial fungi in Narmada river - Upadhyaya, Aradhana; Singh, Jaya; Tiwari, Jayram; Gupta, Saurabh (International Multidisciplinary Research Journal, 2012)
Present study was undertaken to find out the number of water borne conidial fungi in river Narmada at Amarkantak region. The dominant water borne conidial fungi Lunulospora curvula and Triscelephorus monosporus were found 90% of fungi were found in leaves. Total of 35 fungi were recorded form foam, leaves, and twig analysis.